Hollow shell-in-shell Ni3S4@Co9S8 tubes derived from core–shell Ni-MOF-74@Co-MOF-74 as efficient faradaic electrodes. Issue 7 (24th January 2018) - Li, Hui; Yue, Fan; Xie, Hongtao; Yang, Chao; Zhang, Yi; Zhang, Liugen; Wang, Jide
Abstract : Unique shell-in-shell hierarchical structures fabricated through transition from core–shell MOFs would have great potential for hybrid supercapacitor applications. Abstract : This paper reports the novel design of shell-in-shell Ni3 S4 @Co9 S8 double-shelled tube (DST) hierarchical structures with different shell compositions, and the subsequent attempt to fabricate these structures. We fabricated such unique shell-in-shell hierarchical structures through transition from isomorphic metal–organic framework core–shell structures of Ni-MOF-74@Co-MOF-74 in the presence of Na2 S under solvothermal conditions. The as-prepared Ni3 S4 @Co9 S8 DSTs demonstrated high specific capacity (up to 1257.4 F g −1 at a current density of 4 A g −1 ) with excellent charge–discharge reversibility (with 81.5% capacity retention after 1000 cycles), which is superior to that of the single-shelled Co9 S8 tubes (337.8 F g −1 at 1 A g −1 ). The specific capacity of the prepared DST electrode also showed exceptional performance at a current density of 20 A g −1 . Approximately 74.0% of the obtained value of the specific capacity was retained at 1 A g −1 . This approach is a facile method to produce novel electrode materials for energy storage devices and a useful self-templated strategy for the preparation of multi-shelled hollow materials with different shell compositions for different functions.